Water Soluble Antioxidative Crude Polysaccharide From Russula senecis Elicits TLR Modulated NF-κB Signaling Pathway and Pro-inflammatory Response in Murine Macrophages - Khatua, Somanjana; Acharya, Krishnendu (Frontiers in Pharmacology, 2018)
Russula senecis has recently been reported as a new addition to macrofungal flora of West Bengal. Besides, it also emerged as a seasonal health promoting nutrient to local ethnic people and enlisted for the first time as tribal food in our previous publication. In this context, the present work was designed to establish such usefulness scientifically and to meet the aim, crude polysaccharide, Rusenan, was prepared using conventional heated water reflux. Initially, the polymers were characterized to determine chemical composition and for that spectrophotometry along with Fourier-transform infrared spectroscopy (FT-IR), high-performance thin-layer chromatography (HPTLC) and gas chromatography-mass spectrometry (GC-MS) were performed. Analysis indicated that Rusenan was consisted mainly of carbohydrate conjugated with trace amount of protein. Furthermore, glucose was detected as the major monosaccharide (mainly in β-type glycosidic linkage) while other monomers were presented in the order of galactose> mannose> xylose> rhamnose. Conversely, antioxidant potential was determined following eight in vitro systems where the fraction evidenced strong superoxide, hydroxyl, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging activity, high affinity to Fe2+ as well as instant ability to donate electron with EC50 values ranging from 80-3885 µg/ml concentration. In addition, effect on murine macrophages was also investigated where the polysaccharide treatment increased cell proliferation, phagocytic activity, filopodia or lamelipodia formation, nitric oxide (NO) production and reactive oxygen species (ROS) synthesis. Thereafter, through reverse transcriptase polymerase chain reaction (RT-PCR) analysis, significant increase in the expression of Toll like receptor (TLR)-4, TLR-2 and nuclear factor kappa B (NF-κB) was observed; as a result alleviated level of cyclooxygenase (COX)-2, inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF)-α, IκB-α and interferon (IFN)-ᵧ were also noticed explaining definite immune-stimulatory activity of the fraction. Thus, overall finding suggest that R. senecis can be considered as a functional food and may be used in preparation of dietary supplement to enhance general health.